Genetic diversity and community of endophytic actinomycetes within the roots of Aquilaria crassna Pierre ex Lec assessed by Actinomycetes-specific PCR and PCR-DGGE of 16S rRNA gene - Nimnoi P. (2014)
PCR-denaturing gradient gel electrophoresis (DGGE) was used to determine diversity and community of endophytic actinomycetes distributed within the roots of Aquilaria crassna Pierre ex Lec (eaglewood). DNA was extracted from plant roots collected from one plantation in Nakhonnayok province and three plantations in Phetchabun province of Thailand. A nested-PCR was used to specifically amplify all actinobacterial groups. PCR-DGGE analysis of a variable region 3 (V3) of 16S rDNA confirmed the presence of endophytic actinomycetes in genera Nocardia, Pseudonocardia, Streptomyces and Actinomadura within the roots of eaglewood from Phetchabun province. Actinomycetes in genera Nocardia, Nonomuraea, Pseudonocardia and Actinomadura were found to inhabit abundantly in the roots of eaglewood from Nakhonnayok province. Actinobacterial community structures within the roots of this plant grown in two provinces were different from each other based on the generated dendrogram and Sorensen's index. These results suggest that different locations resulted in different endophytic actinomycetes communities within the plant. Besides actinobacterial community structure, genetic diversity was analyzed based on species diversity and simple index. DGGE exhibited many species of actinomycetes inhabited as endophytes. The highest diversity of endophytic actinomycetes was found in the roots from a plantation in Nakhonnayok province and one of the plantations in Phetchabun province. This is the first report of the ecology and the community of endophytic actinomycetes colonized and imbedded within the roots of eaglewood plant. © 2010 Elsevier Ltd.